Agroclimatic Metrics for the Main Stone Fruit Producing Areas in Spain in Current and Future Climate Change Scenarios: Implications From an Adaptive Point of View - Egea, Jose A.; Caro, Manuel; García-Brunton, Jesús; Gambín, Jesús; Egea, José; Ruiz, David (Frontiers in Plant Science, 2022)
Stone fruit production has enormous economic importance in Spain. Cultivation locations for these fruit species (peach, apricot, plum and sweet cherry) cover wide and climatically diverse geographical areas within the country. Climate change is already producing an increase in average temperatures with special intensity in certain areas like the Mediterranean ones. These changes lead to a decrease in the accumulated chill, which can have a profound impact on the phenology of Prunus species like stone fruits due to e.g. difficulties to cover the chilling requirements to break endodormancy, the occurrence of late frost events or abnormal early high temperatures. All these factors can severely affect fruit production and quality and therefore provoke very negative consequences from the socio-economic point of view in the incumbent regions. Thus, characterization of current cultivation areas in terms of agroclimatic variables (e.g. chill and heat accumulation and probabilities of frost and early abnormal heat events), based on data of 270 weather stations for the last twenty years, is carried out in this work to produce an informative picture of the current situation. Besides, future climatic projections from different Global Climate Models (data retrieved from the Meteorological State Agency of Spain – AEMET) up to 2065 for two Representative Concentration Pathway scenarios (RCP4.5 and RCP8.5) are also analysed. Using the current situation as a baseline and considering the future scenarios, information on the current and future adaptive suitability of the different species/cultivars to the different growing areas can be inferred. This information could be the basis of a decision support tool to help the different stakeholders to take optimal decisions regarding current and future stone fruit or other temperate species cultivation in Spain.